PROCEDURAL AND FUNCTIONAL MODEL COMPETENCE OF FUTURE INFORMATION EXPERTS PYROTECHNICS - Жарова, О. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
In the article the model of forming of informative competence of future specialists of radiotricians is examined in a technical university. Structural and functional component models, terms and stages of forming of professional competence of future radiotricians, are distinguished